New User Special Price Expires in

Let's log you in.

Sign in with Facebook


Don't have a StudySoup account? Create one here!


Create a StudySoup account

Be part of our community, it's free to join!

Sign up with Facebook


Create your account
By creating an account you agree to StudySoup's terms and conditions and privacy policy

Already have a StudySoup account? Login here

Product, Quotient Rule, Trigonometric Derivatives

by: Megan steltz

Product, Quotient Rule, Trigonometric Derivatives Math 120-4

Marketplace > Eastern Michigan University > Math > Math 120-4 > Product Quotient Rule Trigonometric Derivatives
Megan steltz
GPA 3.28

Preview These Notes for FREE

Get a free preview of these Notes, just enter your email below.

Unlock Preview
Unlock Preview

Preview these materials now for free

Why put in your email? Get access to more of this material and other relevant free materials for your school

View Preview

About this Document

product rule quotient rule trigonometric derivatives also contain proofs for the product and quotient rule
Calculus I
John G. Patrick
Class Notes
Math, Calculus, Product, Derivatives calculus
25 ?




Popular in Calculus I

Popular in Math

This 6 page Class Notes was uploaded by Megan steltz on Sunday October 9, 2016. The Class Notes belongs to Math 120-4 at Eastern Michigan University taught by John G. Patrick in Fall 2016. Since its upload, it has received 4 views. For similar materials see Calculus I in Math at Eastern Michigan University.


Reviews for Product, Quotient Rule, Trigonometric Derivatives


Report this Material


What is Karma?


Karma is the currency of StudySoup.

You can buy or earn more Karma at anytime and redeem it for class notes, study guides, flashcards, and more!

Date Created: 10/09/16
Product Rule If F(x)=f(x)g(x), Then F’(x)=f(x)g’(x) + f’(x)g(x) Ex. d/dx [ (4x^3 - x^2 -1)(x^3 -2x^2 + 3x +1)] = (4x^3 - X^2 - 1) (3x^2- 4x + 3) = (12x^2 -2x)(x^3 - 2x^2 + 3x + 1) However the product rule is more useful for the product of different types of functions Ex. f(x)= x^2cos(x) g(x) = e^x arctan(x) Proof of the Product Rule Let F(x) = f(x)g(x) F’(x) = lim ((F(x + h ) - F(x))/h) h 0 =lim ((f(x + h )g( x + h) - f(x)g(x))/h) h 0 Subtract and add f(x + h)g(x) = lim ((f( x + h)g(x + h) - f(x + h)g(x) + f(x + h) - g(x) - f(x)g(x))/h) h 0 = lim ((f( x + h)(g( x + h) - g(x)) + g(x)(f( x + h) - f(x))/h) h 0 = lim ((f ( x+ h)(g( x + h) - g(x))/h) + (g(x)f(x + h) - f(x)/h) h 0 = lim (f( x + h) lim ((g(x + h) - g(x))/h) + lim (g(x))lim((f(x + h) - f(x))/h) h 0 h 0 h 0 h 0 = f(x)g’(x) + g(x)f’(x) The Quotient Rule d/dx (f(x)/g(x)) = g(x)d/dx f(x) - f(x)d/dx (g(x))/(g(x))^2 If F(x) = f(x)/g(​ ’(x) = (g(x)f’(x) - f(x)g’(x))/(g(x)^2) Rhyme for remembering quotient rule “ Low times d-high minus high. D-low, over the square of what’s below” Ex. d/dx [x/x^2-1] = ((x^2-1)(1) - x(2x))/(x^2-1)^2 = (x^2 - 1 - 2x^2)/ ( x^4 - 2x^2 + 1) = (- x^2 - 1)/ ( X^4 - 2x^2 + 1) d/dx( x^2 + 2x)/(x^4 - 3x^2 + 1) = ((x^4 - 3x^2 +1)(2x + 2) - (x^2 + 2x)(4x^3 - 6x))/(x^4 - 3x^2 + 1)^2 Graph Note. ​with a function like f(x) = 3/ = 3/x^½ It is easier to rewrite it a 3x^-½ and use the power rule =f’(x) = -(3/2)x^-3/2 Using the quotient rule F’(x) = (x^(½)(0) - 3(½)x^-½)/(x^½) d/dx(x^½(1-x^5) The answer for the power rule and the quotient rule are the same Derivatives of Trigonometric Functions At x = -3π/2, − π/2, π/2, 3π/2, ...., f’(x) must be zero On the interval ( − π/2, π/2,) sin(x) is increasing so f’(x) is positive On (π/2, 3π/2) f’(x) must be negative It looks like d/dx sin(x) = cos(x) By the same method we could guess that d/dx(cos(x))= -sin(x) Thm ​d/dx(sin(x)) = cos(x) Proof d/dx(sin(x)) = lim ((sin( x + h) - sin(x))/h) h 0 Using the addition formula for sin(x) = lim (sin(x)cos(h) + cos(x)sin(h) - sin(x))/h) h 0 = lim ((sin(x)cos(h)-sin(x))/h) + (cos(x)sin(h))/h) h 0 =lim((sin(x)cos(h)-1)/h) + cos(sin(h)/(h) h 0 = lim (sin(x)lim((cos(h)-1)/h) } this is equal to zero h 0 h 0 lim(cos(x))lim(sin(h)/h) } this is equal to one h 0 h 0 = sin(x)*0 = cos(x) * 1 =cos(x) A mass on the end of a spring is pulled down 1 foot and released at time = 0. It moves in s ​ imple harmonic motion Its displacement at time t is given by s(t)= -cos(t) It velocity at time t is given by v(t) = s’(t) = sint(t) t 0 π/2 π 3π/2 2π s(t) -1 0 1 0 -1 v(t) 0 1 0 -1 0 To find d/dx (tan(x)), we use the quotient rule d/dx (tan(x)) = d/dx(sin(x)/cos(x)) =(cos(x)d/dx sin(x)-sin(x)d/dx cos(x))/(cos(x))^2 = (cos(x)cos(x) - sin(x)-sin(x))/cos^2(x) = (cos^2(x) + sin^2(x))/cos^2(x) = 1/cos^2(x) = 1/cos^2(x) = sec^2(x) Graph of tan(x) graph of sec^2(x) To find d/dx sec(x), use the quotient rule d/dx sec(x) = d/dx(1/cos(x)) = (cos(x)(d/dx(1)) - 1*d/dx(cos(x)))(cos(x)^2) = (cos(x)*0 -1 *(-sin(x))/cos^2(x) = (sin(x))/(cos^2(x) = (1/(cos(x))* (sin(x))/(cos(x) = sec(x)tan(x) Ex. d/dx(tan(x)/x^2 = (x^2 d/dx(tan(x))-tan(x)d/dx(x^2))/(x^2)^2 = (x^2sec^2(x)-tan(x)*2x)x^4 =(xsec^2(x)-2tan(x))x^3


Buy Material

Are you sure you want to buy this material for

25 Karma

Buy Material

BOOM! Enjoy Your Free Notes!

We've added these Notes to your profile, click here to view them now.


You're already Subscribed!

Looks like you've already subscribed to StudySoup, you won't need to purchase another subscription to get this material. To access this material simply click 'View Full Document'

Why people love StudySoup

Bentley McCaw University of Florida

"I was shooting for a perfect 4.0 GPA this semester. Having StudySoup as a study aid was critical to helping me achieve my goal...and I nailed it!"

Kyle Maynard Purdue

"When you're taking detailed notes and trying to help everyone else out in the class, it really helps you learn and understand the I made $280 on my first study guide!"

Steve Martinelli UC Los Angeles

"There's no way I would have passed my Organic Chemistry class this semester without the notes and study guides I got from StudySoup."

Parker Thompson 500 Startups

"It's a great way for students to improve their educational experience and it seemed like a product that everybody wants, so all the people participating are winning."

Become an Elite Notetaker and start selling your notes online!

Refund Policy


All subscriptions to StudySoup are paid in full at the time of subscribing. To change your credit card information or to cancel your subscription, go to "Edit Settings". All credit card information will be available there. If you should decide to cancel your subscription, it will continue to be valid until the next payment period, as all payments for the current period were made in advance. For special circumstances, please email


StudySoup has more than 1 million course-specific study resources to help students study smarter. If you’re having trouble finding what you’re looking for, our customer support team can help you find what you need! Feel free to contact them here:

Recurring Subscriptions: If you have canceled your recurring subscription on the day of renewal and have not downloaded any documents, you may request a refund by submitting an email to

Satisfaction Guarantee: If you’re not satisfied with your subscription, you can contact us for further help. Contact must be made within 3 business days of your subscription purchase and your refund request will be subject for review.

Please Note: Refunds can never be provided more than 30 days after the initial purchase date regardless of your activity on the site.